A Survey Paper on Internet of Things and its Data Security Issues - Gurumanapalli, Krishna Priya; Nagendra, M (International Journal of Computer Sciences and Engineering, 2025)
Data is the driving force in this modern digital era. There are numerous platforms available to send a data from one place to another through computer networks. This survey paper classifies and describes the network classification based on topology, connectivity, and geographic area. A brief introduction on Wireless Sensor Network (WSN) and Internet-of-Things (IoT) has been detailed based on the research. These two technologies are identified as a platform for data processing through different sensors. The data sent through the network using different platform contains all kinds of sensitive information. It is the responsibility of the technology providers to build suitable security systems that assure data privacy. This research paper has focused on a detailed investigation of the Internet-of-Things (IoT) and its data security. Different techniques used for data security are listed, among them, an Encryption technique is found to be effective and well suitable for IoT. This research paper presents the survey of some encryption algorithms. Advanced Encryption Standard (AES), Data Encryption Standard (DES), and Rivest-Shamir-Aldeman (RSA) encryption techniques are briefed